User Education - Main Goal of the Academic Libraries - Popović, Aleksandra (Infotheca - Journal for Digital Humanities; Vol 5 No Special is (2004): Infotheca - Journal of Informatics and Librarianship, 2024)
The University of Malaya Library for several years has the tradition of running the Information Skills Course.It has been made compulsory subject for all first year students undertaking a first degree in the University of Malaya since the 1998/1999 academic session. Students are obliged to take part and pass the exam in order to obtain an academic degree. With the exam introduction all the other librarians, beside reference librarians, are included in the teaching process. In the paper are described preparation of the course,results and evaluation of the course and comments of the library.